LANGUAGE LEARNING STRATEGIES USED BY LEARNERS IN LEARNING SPEAKING - Yuli Rachmawati (Journal of English and Education, 2013)
This study is a descriptive study investigating learners’ language learning strategies (LLS) in learning speaking and the different strategies used by the high and low achievers of the class. The study used a descriptive method. Since the data for the study are both in the form of words and numbers, a mixed method design has been employed. To collect the data, a modified questionnaire of SILL, score recording, and interviews are used. The findings show that compensation strategies (M=3,48) are the most frequently used strategies employed by all learners. Meanwhile differences in the strategies used by the high and low achievers in speaking are found in terms of the frequency of use, strategy category, and varieties of strategy. Keywords: Language learning strategy, speaking, exemplary class, high achiever, low achiever